Toxoplasma gondii Infection Induces High Mobility Group Box 1 Released from Mouse Macrophages - Wang, Hui; Li, Muzi; Liu, Jing; Xu, Jianhai; Han, Qian; Liu, Qun (Frontiers in Microbiology, 2017)
High mobility group box 1 (HMGB1) is abundantly expressed in intracellular engaged DNA binding ability. However, more importantly, it is a weapon against infection through proinflammatory response and immune regulation while released to extracellular. Toxoplasma gondii causes inflammatory pathological changes including ileitis and encephalitis in chronic infection. To investigate whether HMGB1 contributes to the toxoplasmosis lesions, we examined HMGB1 changes during T. gondii infection. The results showed that HMGB1 transcription was down-regulated in the murine macrophage ANA1 cell line and mouse peritoneal macrophages (PMΦs) after T. gondii inoculation, but up-regulated in the IFN-γ treated macrophages and the intraperitoneal exudate cells from the T. gondii infected mice. The content of intracellular HMGB1 are basically consistent with the transcription levels in ANA1 assay, while there were no obvious changes in the mouse PMΦs. Both ANA1 and mouse PMΦs released HMGB1 after parasites infection, and no obvious HMGB1 aggregation in cytoplasm compare to the IFN-γ treatment group.. Furthermore, we demonstrated that T. gondii invasion led to HMGB1 release, which was dependent on the Caspase 1 activity. These finding should promote to further investigate the functions of extracellular HMGB1 in the toxoplasmosis.